Peran Islamic Work Ethic Pada Kinerja Karyawan Dengan Di Moderasi Religiusitas - Purnomo, Istiar; Nasor, Nasor; Anggraeni, Erike (ITB AAS INDONESIA Surakarta, 2023)
The Islamic banking industry in the country is showing good growth, but on the other hand, there are several strategic issues that are still hindering the growth of the Islamic banking business, the quality and quantity of human resources is not optimal. Human resources are a central factor in a company and human resources that can compete really help companies achieve their goals so as to produce good performance. This research was conducted with the aim of looking at the important role of Islamic Work Ethic on employee performance and moderated by religiosity whether religiosity can strengthen or weaken the relationship to employee performance. This research includes quantitative research with a moderating approach. The research was conducted at Sharia Bank of Indonesia (BSI) in Bandar Lampung City. The data used is primary data obtained from employees of Islamic banks using questionnaires sent via the Google form application. The sampling technique used is random sampling. Data analysis using SmartPLS 3.0. The results of the study show that Islamic Work Ethic has an influence on employee performance. Religiosity strengthens the influence of Islamic Work Ethic on employee performance.